PEMANFAATAN PERANGKAT DIGITAL DALAM MANAJEMEN SEKOLAH: LITERATURE REVIEW - Adrianus TH. Mahulae; Binur Panjaitan (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
Digital transformation in education has changed the way schools manage operations, administration, and strategic decision-making. Digital tools such as school management information systems, cloud-based platforms, and mobile applications are increasingly being adopted to improve the efficiency and effectiveness of education management.  This study aims to identify, analyze, and synthesize literature on the use of digital tools in school management, including the types of technology used, benefits, challenges, and best practices for implementation. The literature review was conducted through a comprehensive search of 10 articles in the Google Scholar database. The analysis identified five main categories of digital tools: (1) School Management Information Systems, (2) Web portals and cloud platforms, (3) Communication and community tools, (4) Governance and planning dashboards, and (5) Mobile and hybrid applications. The main benefits include increased operational efficiency, data-driven decision making, better stakeholder communication, and professionalization of school leadership. ABSTRAK Transformasi digital dalam pendidikan telah mengubah cara sekolah mengelola operasional, administrasi, dan pengambilan keputusan strategis. Perangkat digital seperti sistem informasi manajemen sekolah, platform berbasis cloud, dan aplikasi mobile semakin banyak diadopsi untuk meningkatkan efisiensi dan efektivitas manajemen pendidikan.  Penelitian ini bertujuan untuk mengidentifikasi, menganalisis, dan mensintesis literatur tentang pemanfaatan perangkat digital dalam manajemen sekolah, termasuk jenis teknologi yang digunakan, manfaat, tantangan, dan praktik terbaik implementasi. Literature Review dilakukan dengan pencarian komprehensif di database Google Scholar sebanyak 10 artikel. Analisis mengidentifikasi lima kategori utama perangkat digital: (1) Sistem Informasi Manajemen Sekolah, (2) Portal web dan platform cloud, (3) Alat komunikasi dan komunitas, (4) Dashboard tata kelola dan perencanaan, dan (5) Aplikasi mobile dan hybrid. Manfaat utama meliputi peningkatan efisiensi operasional, pengambilan keputusan berbasis data, komunikasi stakeholder yang lebih baik, dan profesionalisasi kepemimpinan sekolah.